The civil standard of proof: What is it, actually? - Mark Schweizer (Max Planck Institute for Research on Collective Goods, 2013)
Common Law distinguishes two standards of proof applicable in civil and criminal matters, respectively. The criminal standard of beyond reasonable doubt is much higher than the preponderance of the evidence standard used in civil cases. Continental European Civil Law, on the other hand, recognizes just one standard of full conviction applicable in both criminal and civil cases. This study is the first to look at the standard of proof actually used by judges and judicial clerks in a Civil Law country (Switzerland). It is shown that, when asked directly, the members of court express a high decision threshold in line with legal doctrine and case law. But when Swiss judges are asked to estimate the error costs associated with each outcome and the error-cost-minimizing decision threshold is calculated based on the responses, the resulting standard is no different from the Common Law's preponderance of the evidence standard. When using the stated degree of belief in the truth of the plaintiff's allegations as a predictor for the grant of the plaintiff's request in a civil action, the probability of grant is 50% at a stated conviction of only 63%. It is further shown that the decision threshold is influenced by the individual's loss aversion, with individuals with a higher loss aversion having a higher decision threshold. No difference between the estimated decision threshold for members of the courts and members of the general population is found. The results suggest that the standard of proof actually employed by Swiss judges is not much different from the Common Law's preponderance of the evidence standard, despite the doctrinal insistence to the contrary.
Keywords: 330